2015
DOI: 10.2172/1233732
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Chemical Cleaning Methods for High Level Waste Tanks: Simulant Studies

Abstract: We gratefully acknowledge the assistance of Holly Hall in the movement of equipment, supplies, samples, and chemicals between laboratories during testing. The efforts of Whitney Riley in analyzing most of the non-radioactive test samples are appreciated. SRNL-STI-2015-00517 Revision 0 vi SRNL-STI-2015-00517 Revision 0 vii oxalic/nitric acid reagent. Following treatment using the baseline oxalic acid reagent, detectable levels of actinide removal were achieved using the acidic permanganate cleaning method. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The observation of nickel oxalate is consistent with simulant testing which indicated the formation of the same phase during contact of nickel hydroxide reagent with oxalic acid. 13 XRD results for the OOAC tests (both direct and pretreated) revealed the presence of the same crystalline phases in each sample (though a large amorphous peak was also observed for the P-OOAC sample). Both samples contained hematite and the previously unobserved trimetallic sludge phase trevorite, NiFe 2 O 4 .…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…The observation of nickel oxalate is consistent with simulant testing which indicated the formation of the same phase during contact of nickel hydroxide reagent with oxalic acid. 13 XRD results for the OOAC tests (both direct and pretreated) revealed the presence of the same crystalline phases in each sample (though a large amorphous peak was also observed for the P-OOAC sample). Both samples contained hematite and the previously unobserved trimetallic sludge phase trevorite, NiFe 2 O 4 .…”
Section: Resultsmentioning
confidence: 77%
“…However, within four days after contact of the reagents with Tank 5F sludge samples, the purple color of the permanganate in the more dilute reagent was observed to disappear, indicating a reaction between permanganate and reductants in the waste (such as oxalate anions). Subsequent analysis of the filtered solutions from these tests at approximately 4, 12, and 14 days (Table 3 -8) revealed that the plutonium concentrations observed for the dilute permanganate solution ranged from 3E-07 to 8E-07 M while the concentrations observed for the more concentrated permanganate reagent (0.05 M) ranged from 2E-06 to 3E-06 M. For comparison, plutonium concentrations observed by this method using radioactive simulants were near 7E-06 M. 13 As shown in Table 3-9, the plutonium concentrations observed for the more concentrated permanganate reagent correspond to only 3-4% removal of plutonium from the sample.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations